Students' Perceptions About Teachers' Competence Through Student Learning Motivation and its Implications on Learning Outcomes of Economic Subjects - Fahmi Faqih Nugraha (Return : Study of Management, Economic and Bussines, 2022)
Background: The problem in this study is about the low economic learning outcomes obtained by students based on the average score of the national exams for SMA Negeri in Kuningan Regency in 2015-2019 which tends to fluctuate. AIM: The purpose of this study was to determine the direct and indirect effect of students' perceptions of teacher competencies consisting of personality, pedagogic, professional, and social competencies on learning motivation and their implications for learning outcomes. Method: This research is quantitative research with a survey method using the Area Probability Sample technique. The population of this research is all students of class XI IPS SMA Negeri in Kuningan Regency, totaling 2,676 students spread over 19 schools. As for the research sample as many as 316 students spread over 10 schools. The data analysis technique used path analysis. Based on the results of the descriptive analysis of student perceptions of teacher competence, learning motivation, and learning outcomes, they are in a good category. The results of path analysis obtained the regression equation = 0.108????1 + 0.301????2 + 0.241????3 + 0.418????4 + 0.355????1 and = 0.064????1 + 0.168????2 + 0.290????3 + 0.276????4 + 0.252???? + 0.342????2. The results of the path analysis show that there is a direct influence on students' perceptions of personality competence at 10.8%, pedagogic competence by 30.1%, professional competence at 24.1%, and social competence by 41.8% learning motivation. The direct influence of students' perceptions of personality competence is 6.4%, pedagogic competence is 16.8%, professional competence is 29% and social competence is 27.6% on learning outcomes. The indirect effect of students' perceptions of personality competence gets a count of 2.24, pedagogic competence count of 4.35, professional competencies get a count of 2.77, and social competence gets a count of 2.97, which means it is greater than table 1.97, which means on the indirect effect of learning outcomes through learning motivation Findings: Students' perceptions of teacher competencies which consist of personality, pedagogic, professional, and social competencies have a positive and significant impact on learning motivation and implications for learning outcomes both directly and indirectly.f